Study of factors associated with incisional hernia in female - Sharma, Vidhyasagar M.; Akruwala, Sushil D. (International Journal of Research in Medical Sciences, 2017)
Background: Incisional hernia is still relatively common in our practice. The aim of the study was to identify risk factors associated with incisional hernia in females in our region. Methods: All the women who presented with incisional hernia between 2010 and 2012 were retrospectively studied using records and preparing a standard form to obtain information on pre-hernia (index) operations and possible predisposing factors. They all had open surgical repair and were followed up for 12-36 months. Results: Fifty two women were treated during study period. The index surgeries leading to the hernias were emergency caesarian section 26/52 (50%), emergency exploratory laparotomy 6/52 (11.6%), and elective surgeries 20/52 (38.5%). Major associated risk factors were the use of wrong suture materials for fascia repair, midline incisions, wound sepsis, and overweight. Conclusions: For elective surgeries, reduction of weight should be encouraged when appropriate, and transverse incisions are preferred. Absorbable sutures should be avoided in fascia closure. Antibiotics should be used for complicated cases.